Autonomous self-healing multiwalled carbon nanotube nanocomposites with piezoresistive effect. Issue 33 (7th April 2017) - Wu, Tongfei; Chen, Biqiong
Abstract : Viscoelastic rubber reinforced by multiwalled carbon nanotubes exhibited rapid, autonomous, mechanically and electrically self-healing properties and piezoresistive behavior. Abstract : Autonomous self-healing fatty acid rubber nanocomposites reinforced by multiwalled carbon nanotubes (MWCNTs) were synthesized by solution blending. The dispersion of MWCNTs in the self-healing fatty acid rubber matrix was observed by scanning electron microscopy. The reinforcement of MWCNTs on the mechanical properties and the self-healing capability of the self-healing fatty acid rubber/MWCNT nanocomposites were investigated by tensile testing. The effect of MWCNT concentration on the electrical conductivity of self-healing fatty acid rubber was studied and the electrically conductive behaviors of self-healing fatty acid rubber/MWCNT nanocomposites were interpreted using the percolation theory and tunneling model. The piezoresistive effect was observed in the nanocomposite with 19.7 vol% MWCNTs, which demonstrates potential for pressure sensing applications.